Case report: Self-restraint in a patient with alien hand syndrome following cerebral infarction involving the anterior cerebral artery territory - Sugawara, Kazuhiro; Takeuchi, Toshiki; Harada, Kuniaki; Taki, Marina; Fujimura, Ikumi; Kogami, Yuichi; Furuta, Ryoichi (Frontiers in Neurology, 2023)
Frontal alien hand syndrome (AHS) presents as impulsive grasping and groping and compulsive manipulation of environmental objects that can affect the dominant or nondominant hand. A few reports have shown improvements in neuropsychological scores over time when self-restraint of the right hand AHS was enforced. A 72-year-old woman presented with right-handed involuntary instinctive grasping reactions and compulsive manipulation of tools after an infarction of the frontal lobe and corpus callosum (CC). She was diagnosed with cerebral infarction involving the anterior cerebral artery territory and a frontal variant of AHS. At AHS onset, the patient was unaware that her right hand was moving against her will; she was only aware that her right hand was moving when the therapist pointed it out to her. Later, she began to recognize that her right hand was involuntarily moving, and she could restrain the movement of her right hand with her left hand. Approximately 5 months following AHS onset, the patient could voluntarily restrain her AHS symptoms by telling her right hand not to move against her will in her head. Most neuropsychological scores improved by 5 months following AHS onset. However, the patient showed disruptions in the genu and midbody of the left cingulate cortex, as shown via diffusion tensor imaging (DTI), and the sensation of the “right hand moving by itself” remained even 5 months after AHS onset. Although damage to the CC fibers was evident on DTI at 5 months following onset, the patient exhibited no sensory deficits and demonstrated good hand ownership as well as early improvement in attention and cognitive dysfunction. Therefore, the patient recognized her AHS symptoms, which included her hand moving against her will, and was able to consciously restrain her hand movement.